Capabilities in strategic knowledge sourcing and assimilation: a new look at innovation in the automotive industry. (1st January 2001) - Birchall, David W.; Tovstiga, George; Chanaron, Jean-Jacques
The auto industry is undoubtedly one of the most competitive industries and has undergone significant change but the predominant paradigm remains the gasoline engine. Notwithstanding its aged paradigm, the industry is being forced to transform itself as it is being hurled into the new economy. The recent announcement of General Motors', Ford's and DaimlerChrysler's launching of a joint mammoth online exchange for automotive parts and supplies is just one of many examples of how tradition-bound old economy firms are joining hands with long-time bitter rivals to compete in the new economy online marketplaces. The rhetorical question is, will they finally learn to get along? Or perhaps more to the point, what will it take for these former rivals to build new positions of collaborative competitive advantage? In this paper, the authors pursue this question. By examining innovation in the auto industry, they explore the degree to which the predominant industry paradigm is being challenged. The auto industry has increasingly outsourced its innovation in product development, including systems integration. Confronted with innovations in ICT which are set to change radically the functionality and use of the motor vehicle and at the same time redefine the industry, the auto manufacturers are at a strategic inflection point between the two economies. Totally new capabilities as well as the refinement of many existing capabilities will be essential if these auto companies are to retain a dominant position in their supply chains.